Legal and regulatory environment for electronic information - Oppenheim, Charles (Infonortics CalneGB, 1995)
Focuses on data bases, the Internet and real-time information. Covers copyright, pornography, libel and slander on the Internet. Includes image copyright as well as some implications of the tension between copyright law and the networked world. Looks at the broader picture of national information policies.